2013
DOI: 10.1186/1471-2377-13-106
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan limits reperfusion injury in a rat middle cerebral artery occlusion (MCAO) model

Abstract: BackgroundNeuroprotective strategies in ischemic stroke are an important challenge in clinical and experimental research as an adjunct to reperfusion therapy that may reduce neurologic injury and improve outcome. The neuroprotective properties of levosimendan in traumatic brain injury in vitro, transient global brain ischemia and focal spinal cord ischemia suggest the potential for similar effects in transient brain ischemia.MethodsTransient brain ischemia was induced for 60 min by intraluminal occlusion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
1
13
0
3
Order By: Relevance
“…Previous nonclinical studies have shown some effects of levosimendan on the brain (Hein et al, 2013;Roehl et al, 2012). Moreover, a recent report showed that levosimendan was beneficial in a model of injury to the immature brain following cardiopulmonary bypass (Namachivayam et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Previous nonclinical studies have shown some effects of levosimendan on the brain (Hein et al, 2013;Roehl et al, 2012). Moreover, a recent report showed that levosimendan was beneficial in a model of injury to the immature brain following cardiopulmonary bypass (Namachivayam et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Because of the narrow time window as demonstrated in experimental studies, one has to consider that such a drug, for induction of postconditioning, should be administered before reperfusion so that it is circulating in blood at the time of onset of reflow (Andreadou 2008). Literature is replete with studies involving neuroprotection with pharmacological agents administered at the start of reperfusion (Sicard et al 2009;Du et al 2010;Tong et al 2011;Hein et al 2013;Bouhidel et al 2014;Zhang et al 2016). However, it has been debated whether this approach can be described as 'pharmacological postconditioning' or 'post-reperfusion treatment' (Sandu and Schaller 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly owing to this unique characteristic, several clinical trials or meta-analyses have implied favorable benefits, including improved cardiac function and reduction of mortality or length of hospital stay, upon levosimendan treatment when compared with dobutamine treatment in critically ill patients or those with a cardiology setting (34)(35)(36)(37). The neuroprotective effect of levosimendan has been recently demonstrated in a TBI in vitro model (38), and in a cerebral reperfusion and spinal cord injury in vivo model (39,40). The exact mechanism is unclear, and is possibly attribute to the opening of ATP-sensitive K + channels (mitoKATP channels) and to the suppression of nitric oxide synthase expression, cell death and inflammatory response upon the application of levosimendan (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%